EVALUATION OF ANTI-INFLAMMATORY EFFECT OF BELLADONNA (A HOMEOPATHIC DRUG) IN EXPERIMENTAL ANIMALS-RATS - YAKAIAH VANGOORI; SWATHI.JANAPATI (International Journal of Pharma and Bio Sciences, 2013)
To evaluate the anti-inflammatory effect of Belladonna on acute and chronic inflammatory experimental animal models (rats). The Belladonna, a homeo preparation was tested for its efficacy in acute and chronic inflammatory rats. In acute models: rat paw edema method was used. rats were divided into 4 groups 6 rats each. Group-I (NC), received 2% GA 2ml, Group-II (PC) received Aspirin (200mg/Kg.), Group-III, IV received Low dose (6CH) & High dose (200CH) of Belladonna preparation orally. Edema was developed in injected paw. Immediately the foot edema volume was measured at 0hr and at the end of 3rdhr. The percentage of inhibition of edema by drugs was measured and compared between the Test, Control & Standard groups. In chronic models: granuloma method was used and test drugs were given for 7days.The animals were divided and treated same as in acute model. After 7 days treatment, on 8th day animals were sacrificed each implanted pellet was extracted with adherent granulation tissue. These pellets were dried & weighed. The known weight was deducted from granulation tissue weight. The mean weight of granulation tissue and difference in weight of granulation tissue for each group was calculated and the percentage of inhibition of inflammation was calculated. The percentage of inhibition of edema in acute model with 6CH, 200CH after 3 hrs is 76%, 74% respectively and with Aspirin is 78%. In chronic models, the percentage of inhibition of granulation tissue with 6CH, 200CH after 7 days is 31.57%, 29.99% respectively and with Aspirin is 32.77%. The reduction of inflammation was statistically significant in each group is (P<0.001). Belladonna, a homeo preparation is a best alternative drug for the treatment of acute inflammatory conditions with no side effects.